What Constitutes Rape? The Effect of Marital Status and Type of Sexual Act on Perceptions of Rape Scenarios. (December 2018) - Adams-Clark, Alexis A.; Chrisler, Joan C.
Many people believe that rape is always perpetrated by a stranger and involves vaginal intercourse. To clarify perceptions of rape that do not follow traditional beliefs, participants were presented with a vignette that described a rape in which the marital status and sexual act were manipulated. Participants were then asked to assess the incident's severity and the victim's responsibility. Results indicated that there was no difference in perceptions between vignettes based on marital status. However, rapes involving vaginal intercourse were associated with lesser degrees of victim blame and minimization than were rapes involving forced oral sex or digital sex.